PENGARUH PENGARUH PERTUMBUHAN PENDUDUK, PDRB, EKONOMI, DAN TINGKAT INFLASI TERHADAP PENERIMAAN PAJAK DAERAH PADA KOTA PANGKALPINANG TAHUN 2005-2009 - Siska, Ery; Nizarudin, Abu (Journal of Accountancy FE UBB, 2013)
Local Tax Revenue is fund allocation income not only to fulfill the local expenditure and peopleâs needs economically, but also to prosper them. The costs of local needs cannot be achieved and the society has no profit from the region without it.Â Â Â Â Â Â Â Â Â Â Â This study aims to assess the influence of population growth, Gross Regional Domestic Product, economy, and inflation rate to the local tax revenues in Pangkalpinang. It uses local tax revenue from 2005 to 2009 as the population. Samples are carried out by non-probability sampling method, for instance, purposive sampling with particular consideration. The data is from DPPKAD and BPS Pangkalpinang, and analyzed by multiple regression with SPSS 17.Â Â Â Â Â Â Â Â Â Â Â The result shows that population growth, Gross Regional Domestic Product, economy, and inflation rate (independent variables) have no significant influence simultaneously to the local tax revenue (dependent variable). While, those independent variable impacts significantly in partial to the dependent variable.Â Keywords: Local Tax Revenue, Population Growth, Gross Regional Domestic Product, Economy, and inflation Rate.